Análise do grau de agregação de asfalteno e da formação de emulsão água/óleo através de modelo Coarse-Grain - Silvino, Pedro Felipe Gadelha (2018)
Asphaltenes compounds are the heaviest hydrocarbon fraction in the petroleum and represent a solubility class of compounds that are toluene soluble and n-heptane insoluble. Due changes in pressure, temperature or composition, asphaltenes can precipitate in the formation or in the production and processing equipment, in addition, asphaltenes are some of the main compounds responsible for the stabilization of water/oil emulsions in crude oil. The asphaltene precipitation and the stabilization of emulsions are important petroleum industry issues that increase the production cost. Molecular simulation is an important tool to study the mechanisms involved in these phenomena bring valuable insights to improve the existing methods of precipitation and emulsion prevention. Coarse-Grained (CG) molecular dynamics techniques were applied to simulate the asphaltene precipitation and the stabilization of emulsions with time and space scales compatible with the complexity of these systems. A proposition for an asphaltene molecules CG model for these simulations was parameterized by comparison with atomistic simulations. The behavior of asphaltene at the oil/water interface was studied using the angle between asphaltenes molecules and interface and the density distribution profile. The effect of asphaltene concentration and type on the oil/water interfacial tension was validated. The temporal evolutions of asphaltenes molecules aggregation at several heptane/toluene model oils were evaluated and a simulation-based methodology was applied to determine the onset of asphaltene precipitation. The formation and stabilization of emulsions were simulated, it being possible to determine the minimum amount of asphaltenes necessary to avoid water droplets coalescence. The models and methodologies proposed in this work can be used to represent complex and large petroleum systems by long-time simulations and describe the asphaltene behavior at different conditions.